REVIEW ON MEDICINAL AND PHARMACOLOGICAL PROPERTIES OF IRESINE HERBSTII, CHROZOPHORA ROTTLERI AND ECBOLIUM LINNEANUM - Dipankar, C; Murugan, S; Uma, P Devi (African Journal of Traditional, Complementary and Alternative Medicines, 2011)
India has a rich tradition of plant-based knowledge on healthcare. A large number of plants/plant extracts/decoctions or pastes are equally used by tribals and folklore traditions in India for treatment of cuts, wounds and burns. The resistance of the microorganism has increased due to the indiscriminate use of commercial antimicrobial drugs commonly used for the treatment of infectious diseases. Resistance to antimicrobial agents has resulted in morbidity, mortality, from treatment failures and increased health care costs. There is an urgent need to discover novel, effective plant-based antimicrobial drug to the increasing problem of drug resistance. This situation forced the scientist to search for new antimicrobial substances from various sources including medicinal plants. Iresine herbstii, Ecbolium linneanum , Chrozophora rottleri have been used in folk remedies and is reported to have a broad range of therapeutic effects. Therefore this paper attempts to bridge the lacunae in the existing literature and offers immense scope for researchers engaged in validation of the traditional claims and development of safe and effective therapeutic agent.